2014
DOI: 10.1007/s40333-014-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enclosure management on soil properties and microbial biomass in a restored semi-arid rangeland, Kenya

Abstract: Rangeland degradation is a serious problem throughout sub-Saharan Africa and its restoration is a challenge for the management of arid and semi-arid areas. In Lake Baringo Basin of Kenya, communities and individual farmers are restoring indigenous vegetation inside enclosures in an effort to combat severe land degradation and address their livelihood problems. This study evaluated the impact of enclosure management on soil properties and microbial biomass, being key indicators of soil ecosystem health. Six res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 34 publications
8
35
0
Order By: Relevance
“…Although we did not measure erosion as such, we did measure some reciprocal parameters; the increases in vegetation cover and soil C inside enclosures, which were found by for example Damene et al (2013) in Ethiopia and Mureithi et al (2014) in another area of Kenya, as well as the increasing populations, and the extent of enclosure use in Chepareria, indicate that the title of Tiffen et al's book (1994) might be true also in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not measure erosion as such, we did measure some reciprocal parameters; the increases in vegetation cover and soil C inside enclosures, which were found by for example Damene et al (2013) in Ethiopia and Mureithi et al (2014) in another area of Kenya, as well as the increasing populations, and the extent of enclosure use in Chepareria, indicate that the title of Tiffen et al's book (1994) might be true also in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Means followed by the same letter across each row do not differ significantly at P ≤ 0.05 [32] found that, on average, exclosures lowered the BD of top soil from 1.48 to 1.19 g cm −3 in range lands of Kenya. Mean value for BD varied from 1.12 g cm −3 (in exclosure) to 1.34 g cm −3 (in grazing land) in nearby site [4].…”
Section: Swc Measuresmentioning
confidence: 91%
“…High MBC can also be used as bio-indicator for the recovery of degraded soils [27]. Thus, high MBC in exclosures indicate that they had the potential for the restoration of soil quality [32].…”
Section: Swc Measures Mbc (Mg Kgmentioning
confidence: 99%
See 1 more Smart Citation
“…As a sink, the microbial biomass is a mechanism for immobilizing N, effectively reducing N losses through leaching or associated denitrification [41,42]. In other words, the MBN is an indicator of the immobilization of N by microbes, and is considered a regulator of N dynamics in arid and semiarid regions [41,43]. Fisher et al [15] reported that levels of extractable N (NH 4 + -N and NO 3 − -N) in the Jornada Basin directly decreased after rainfall, which they attributed to increased N immobilization in the microbial biomass, as well as to increased leaching of N. Reynolds et al [9] concluded that extractable N (NH 4 + -N and NO 3 − -N) accumulation during the summer drought in the Jornada Basin could result from the effects of drought upon N immobilization in the microbial biomass and plant access to soil moisture and nutrients.…”
Section: How Did the Variation In Soil N Availability Occur?mentioning
confidence: 99%